2007
DOI: 10.1590/s0100-29452007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Amadurecimento de bananas 'maçã' submetidas ao 1-metilciclopropeno (1-MCP)

Abstract: RESUMO -Objetivou-se avaliar o efeito do 1-MCP, em diferentes tempos de aplicação, sobre amadurecimento e atributos de qualidade da banana 'Maçã'. Utilizou-se um delineamento experimental inteiramente casualizado (DIC), em esquema fatorial 3x5, ou seja, avaliaramse as bananas em três diferentes graus de coloração da casca (grau 2: 100% verdes; grau 4: mais amarelas que verdes; grau 7: completamente amarelas, com pontuações marrons) e cinco tempos de aplicação de 50 hL. L-1 de 1-MCP (0-controle; 6; 9; 12 e 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 8 publications
2
2
0
1
Order By: Relevance
“…However, low starch deposition resulted in similar levels of RSC among the treatments, in terms of P 2 O 5 doses. Fruit peel colour; pH; SSC; TA; malic acid; and ratio found to be similar to those described in the literature for the same cultivar (Pinheiro et al, 2007).…”
Section: Physicochemical Aspects Of Banana Fruitssupporting
confidence: 85%
“…However, low starch deposition resulted in similar levels of RSC among the treatments, in terms of P 2 O 5 doses. Fruit peel colour; pH; SSC; TA; malic acid; and ratio found to be similar to those described in the literature for the same cultivar (Pinheiro et al, 2007).…”
Section: Physicochemical Aspects Of Banana Fruitssupporting
confidence: 85%
“…Sugar content is a main factor of fruits consumption quality and can be influenced by some factors such as sun exposure, irrigation, rootstock and fertilization. The use of 1-MCP did not present statistical difference and this result is in accordance to Corrent et al (2004), Brackmann (2005), and Pinheiro et al (2006), because ethylene does not influence this physiological parameter (Ayub et al 1996).…”
Section: Resultssupporting
confidence: 84%
“…Patricia et al [33] observed increased hydrolysis of soluble pectin in sapodilla cell walls as fruit ripening proceed. Pinheiro et al [34] also found similar 1-MCP effects on soluble and total pectin contents as tomato and bananas ripened. Similarly, delayed softening of peach during storage was directly associated with delayed increase of water-soluble pectin content [35].…”
Section: Discussionmentioning
confidence: 77%